Kinetic Spectrophotometric Procedure for Investigation of Furosemide Drug in Pharmaceuticals Preparations (Global Journal of Medical Research, 2016)
Abstract not found
Keywords: kinetic; spectrophotometric; method; determination; furosemide drug; pharmaceuticals preparations